2019
DOI: 10.1159/000492502
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Parents in Neonatal and Pediatric Research

Abstract: Background: Parents and their infants are the beneficiaries of neonatal and pediatric research, but in the past they have been excluded from most stages of research projects. As a result, many projects may fail to produce the most worthwhile information for parents and families. Lately, veteran resource parents and patients have been increasingly integrated in research initiatives. Methods: Benchmarking of neonatal and pediatric research initiatives where resource parents and/or ex neonatal patients have helpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 39 publications
(50 reference statements)
0
24
0
1
Order By: Relevance
“…In practice, ethics committees require that precise information about the study and about legal aspects of research be mentioned, so shortening the written information is difficult. Yet, the written information can be improved with collaborative work between physicians and parents, by making it more understandable and relevant for non-professionals 26–29. In Europe, the parents’ advisory board of the European Foundation for the Care of Newborn Infants and their family give recommendations about the consent process in neonatal trials 30.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, ethics committees require that precise information about the study and about legal aspects of research be mentioned, so shortening the written information is difficult. Yet, the written information can be improved with collaborative work between physicians and parents, by making it more understandable and relevant for non-professionals 26–29. In Europe, the parents’ advisory board of the European Foundation for the Care of Newborn Infants and their family give recommendations about the consent process in neonatal trials 30.…”
Section: Discussionmentioning
confidence: 99%
“…Some interviewed providers suggested that inviting parents to RECs may provide a solution. Involving parents in the ethical review of study protocols was also recommended by Janvier et al ,35 but actual membership to an REC is considered complex. Janvier et al 35 therefore recommended to start with more easily achievable goals when planning to involve parents in research, such as the revision and improvement of consent forms, collaboration in the selection of research topics, or collaborating in patient recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays MRI with a field strength up to 3.0 Tesla (T) is routinely used in infants. The increase of a field strength of 1.5T to 3.0T has improved MRI quality in infants and enabled us to see more details and pathology (65). In adults, 7.0T has shown to further increase diagnostic value and is now frequently used.…”
Section: Innovative Neuroimaging Methodsmentioning
confidence: 99%
“…We have to discuss the primary outcome of trials with parents and patients. What parents and patients consider as clinically relevant might differ from the opinion of researchers and clinicians (65). The aim of research should be to improve the quality of life of patients and their opinion about how their quality of life can be improved is therefore essential.…”
Section: Patient Participationmentioning
confidence: 99%
See 1 more Smart Citation